Identifying metabolic dysfunction-associated steatotic liver disease in patients with type 2 diabetes mellitus using clinic-based prediction tools - Alkaabi, Juma; Afandi, Bachar; Alhaj, Omar; Kanwal, Darakhshan; Agha, Adnan (Frontiers in Medicine, 2024)
Background Metabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as non-alcoholic fatty liver disease (NAFLD), is a global cause of chronic liver disease. The prevalence of MASLD is high in patients with type 2 diabetes mellitus (T2DM). Various non-invasive tools such as the fibrosis-4 index (FIB-4) and NAFLD fibrosis score (NFS), liver ultrasound, and FibroScan can aid in the detection of liver fibrosis in MASLD, while the Hamaguchi ultrasound-based liver grading system has demonstrated high sensitivity and specificity comparable to liver biopsy. Objective We assessed the frequency of MASLD in patients with T2DM using the liver ultrasound Hamaguchi score and the accuracy of NFS and Fib-4 in identifying MASLD. Patients and methods We retrospectively collected data and reviewed the charts of all patients with T2DM who underwent liver ultrasound and laboratory tests during the past 5 years. Results A total of 6,214 medical records were screened, and only 153 patients (68.6% women; mean age, 59 ± 12.2 years) fulfilled the selection criteria. MASLD was diagnosed using the Hamaguchi grading criteria in 45.1% of patients. A high/intermediate NFS had a higher sensitivity (79.7%) for diagnosing MASLD with a specificity of 10.7%, while a high/intermediate Fib-4 score showed only 30.4% sensitivity but a higher specificity of 54.8%. Conclusion Our study indicates that MASLD is frequent in patients with T2DM, and clinical prediction tools such as NFS and Fib-4 can be applied in clinic/primary care settings with variable results.